ANALISA DAYA DUKUNG PONDASI KACAPURI DI ATAS TANAH GAMBUT YANG DISTABILISASI - Muhammad Afief Ma’ruf; Wiku Adhiwicaksana Krasna; J.C. Heldiansyah (INFO-TEKNIK, 2013)
The traditional society of south borneo has a traditional form of building foundation that has been used for a very long time for their traditional house. This is called Kacapuri foundation that use a combination of Ulin wood and Galam wood. But right now because the lack of Ulin wood, this form is  not familiar anymore in south borneo.The rising in number of people forced the use of peat soil in borneo to be used as an alternative for their settlement. But the natural form of peat soil itself has become a challenge to the construction, therefore needs to be reinforced, one of the method is stabilisation. The optimum composition of lime and rice husk ash used for stabilization is 15% from the peat soil wet unit weight for the peat that got influence by surrounding water.Because of the few things above, the research in kacapuri foundation above the stabilized peat soil is established. From the test conclude that the value of GS rise to 1,584, water content lowered to 221,393 % and the unit weight is rise 1,158 t/m3. Pore value lowered to 3,386 and pH rise to 5,2.From the consolidation test the total settlements and vertical strain is concluded. The total settlements is lowered to 0,18 mm. The shear strength parameter is rise with the cohesion 0,1 and internal friction 30,646o. The ultimate bearing capacity qu for kacapuri foundation above the stabilized peat soil according to terzaghi formula is 87,675 t/m2.